CT planning studies for robotic total knee arthroplasty: what does it cost and does it require a formal radiologist reporting?. (June 2020) - Abdelfadeel, Walaa; Houston, Nicklaus; Star, Andrew; Saxena, Arjun; Hozack, William J.
Abstract : Aims: The aim of this study was to analyze the true costs associated with preoperative CT scans performed for robotic-assisted total knee arthroplasty (RATKA) planning and to determine the value of a formal radiologist's report of these studies. Methods: We reviewed 194 CT reports of 176 sequential patients who underwent primary RATKA by a single surgeon at a suburban teaching hospital. CT radiology reports were reviewed for the presence of incidental findings that might change the management of the patient. Payments for the scans, including the technical and professional components, for 330 patients at two hospitals were also recorded and compared. Results: There were 82 incidental findings in 61 CT studies, one of which led to a recommendation for additional testing. Across both institutions, the mean total payment for a preoperative scan was $446 ($8 to $3, 870). The mean patient payment was $71 ($0 to $2, 690). There was wide variation in payments between the institutions. In Institution A, the mean total payment was $258 ($168 to $264), with a mean patient payment of $57 ($0 to $100). The mean technical payment in this institution was $211 ($8 to $856), while the mean professional payment was $48 ($0 to $66). In Institution B, the mean total payment was $636 ($37 to $3, 870), with a mean patient payment of $85 ($0 to $2, 690). Conclusion: The total cost of a CT scan is low and a minimal part of the overall cost of the RATKA. No incidental findings identified on imaging led to a change in management, suggesting that the professional component could be eliminated to reduce costs. Further studies need to take into account the patient perspective and the wide variation in total costs and patient payments across institutions and insurances. Cite this article: Bone Joint J 2020;102-B(6 Supple A):79–84.